Liquid Scintillation Radioassay in Disposable Microcentrifuge Tubes: Radioimmune Precipitates and Other Applications - Schaffer, F. L. (1974)
A simple, economical radioassay system employing disposable polypropylene microcentrifuge tubes was developed. Plastic adapters permitted automatic operation in liquid scintillation spectrometers. Counting efficiencies of (3)H, (14)C, (32)P, and (125)I in liquid scintillation cocktails and of (32)P by Cerenkov radiation (at lower efficiency in absence of added scintillator) were comparable to those in standard vials. Multipurpose use of the microtubes made the system versatile and expedient, e.g., collection of precipitates and radioassay in the same container. Collection of radioimmune precipitates was aided by a carrier inorganic precipitate, Mg(2)P(2)O(7).